International Transport Corridors and their Impact on the Countries’ Economic Development - Azimov, Rustam (European Journal of Applied Sciences, 2025)
This article discusses the international transport corridors’ concept, goals of establishing and general characteristics. The author provides brief description of prerequisites for the international transport corridors formation and development, and also considers the contribution of international transport corridors to the national economy development of the states participating in the transport and logistics system from the point of view of micro- and macroeconomic indicators. The conclusions contained in this article regarding the international transport corridors importance for the economy of the state can be used in the future to assess the need to develop transport and logistics infrastructure within the framework of already functioning international transport corridors, the formation of new international transport corridors in the context of changing macroeconomic conditions and redistribution of traffic flows. This work may be of interest to researchers in the field of global and regional economics, transport and logistics, international entrepreneurship and public administration.